Factors linked to accessing COVID‐19 recommendations among working migrants. Issue 1 (25th September 2021) - Zlotnick, Cheryl; Dryjanska, Laura; Suckerman, Suzanne
Abstract: Objectives: Guided by the Health Belief Model (HBM), this study explored factors associated with accessing COVID‐19 health information. Design/sample: A cross‐sectional study design was used. Sample: Migrants ( n = 259) employed in Israel prior to the onset of the COVID‐19 pandemic were recruited. Measurements: The on‐line questionnaire included: The Satisfaction with Life Scale, the Brief Resilience Coping Scale and Immigrants' Language Ability scale. Results: Migrants obtaining COVID‐19 information when issued were more likely to have decreased employment or unemployment after COVID‐19 government restrictions (OR = 1.98; CI = 1.03, 3.89; p < .05) and more likely to have a better language ability (OR = 1.20; CI = 1.10, 1.32, p < .0001), but they were less likely to use family and/or friends as their COVID‐19 health resource (OR = 0.54, CI = 0.30, 0.96; p < .05). Migrants encountering the most employment difficulties were: female ( p < .05), older age ( p < .05), unmarried ( p < .01), with unstable finances ( p < .0001), and in Israel less than 5 years ( p < .01). Conclusions: Migrants with more precarious employment had more societal disadvantage (i.e., women, older age, unmarried, poorer socioeconomic status, and newer migrants) and relied on informal and potentially inaccurate, health sources. Public health officials aiming to decrease COVID‐19 infection must improve health information access to all members of society, particularly at‐risk groups such as migrants.